To investigate the effect of adsorbents dose, temperature, pH on initial and final concentration of Chromium and Lead present in water - Gupta, Poonam (Journal of Neonatal Surgery, 2025)
The current research examines the influence of adsorbent dose, temperature, and pH on the removal efficiency of Chromium (VI) and Lead (II) from aqueous solutions by Lemna gibba powder (LGP) as a biosorbent. Lemna gibba, a free-floating aquatic macrophyte that belongs to the duckweed family, is known for its high growth rate, surface area, and rich functional groups like hydroxyl, carboxyl, and amino moieties. The biomass was obtained from a nearby freshwater pond, well washed, oven-dried, powdered, and sieved before application. Batch adsorption experiments were conducted by adjusting adsorbent dose (0.5–2.5 g/100 mL), temperature (20–45°C), and pH (2–8) to assess their impact on removal performance. The best removal efficiency for Cr(VI) was found at an adsorbent dose of 2.0 g/100 mL, pH 5.5, and 40°C temperature (92.5%), while Pb(II) reached maximum removal of 95.1% at pH 6.0 under identical conditions. FTIR and SEM studies indicated that the adsorption process included electrostatic attraction, ion exchange, and surface complexation with LGP's functional groups. These findings indicate that Lemna gibba is a cost-effective, efficient, and environmentally friendly biosorbent with significant potential for use in heavy metal remediation of polluted waters.